Amidation of Carboxylic Acids with Amines by Nb2O5 as a Reusable Lewis Acid Catalyst. Issue 21 (11th September 2015) - Ali, Md. A.; Siddiki, S. M. A. H.; Onodera, Wataru; Kon, Kenichi; Shimizu, Ken‐ichi
Abstract: Among 28 types of heterogeneous and homogenous catalysts tested, Nb2 O5 shows the highest yield for direct amidation of n ‐dodecanoic acid with a less reactive amine (aniline). The catalytic amidation by Nb2 O5 is applicable to a wide range of carboxylic acids and amines with various functional groups, and the catalyst is reusable. A comparison of the results of the catalytic study and an infrared study of the acetic acid adsorbed on the catalyst suggests that activation of the carbonyl group of the carboxylic acid by Lewis acid sites on Nb2 O5 is responsible for the high activity of the Nb2 O5 catalyst. Kinetic studies show that Lewis acid sites on Nb2 O5 are more water‐tolerant than conventional Lewis acidic oxides (Al2 O3, TiO2 ). In comparison with the state‐of‐the‐art homogeneous Lewis acid catalyst for amidation (ZrCl4 ), Nb2 O5 undergoes fewer negative effects from basic additives in the solution, which indicates that Nb2 O5 is a more base‐tolerant Lewis acid catalyst than the homogeneous Lewis acid catalyst. Abstract : Back to base : Nb2 O5 is a general and reusable heterogeneous catalyst for the direct amidation of carboxylic acids with amines as a result of base‐tolerant Lewis acid catalysis of surface Nb 5+ sites. This simple and atom‐efficient method tolerates various functional groups and is applicable to challenging substrates such as anilines and α‐hydroxycarboxylic acids.